2021
DOI: 10.1080/02640414.2021.1945776
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vision impairment on match-related performance and technical variation in attacking moves in Paralympic judo

Abstract: In Paralympic judo for athletes with vision impairment (VI judo) all eligible athletes (i.e. B1, B2 and B3 classes) compete against each other in the same competition. Evidence suggests that athletes with more impairment may be disadvantaged, but that more sensitive measures of performance are necessary to understand the impact of impairment on performance. The aim of this study was to investigate the relationship between Para sport class and technical variation, time-motion variables, and performance in Paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
(49 reference statements)
1
13
0
Order By: Relevance
“…In addition, it was found that sex and weight category were both variables that affected the temporal structure of the combat 16,17,41,42 . When VI was taken into account, it was observed that B1 combats were significantly shorter in comparison with B2 and B3 42,44,45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was found that sex and weight category were both variables that affected the temporal structure of the combat 16,17,41,42 . When VI was taken into account, it was observed that B1 combats were significantly shorter in comparison with B2 and B3 42,44,45 …”
Section: Resultsmentioning
confidence: 99%
“…Seven investigations aimed at determining the temporal structure of the combats through time-motion analysis 16,17,41–45 . According to the existing literature, one study found that compared with what is currently observed in sighted judokas, para-judokas showed shorter working sequences, longer pauses sequences, and a greater recovery time 43 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that B1 athletes have lower competitive performance (e.g., scores and medals in World Championships and Paralympic Games; Kons et al, 2019; Krabben et al, 2018) and impaired technical-tactical and attacks moving performance in Paralympic Games (Kons et al, 2019, 2021). In agreement with these findings, Mashkovskiy and colleagues (2019) found that in the last 10 years, B1 athletes have been losing more often in matches with B2 and B3 athletes among both male and female teams.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations have recently evaluated the performance of judo athletes with visual impairment, focusing on different aspects of seemingly relevant judo performance, particularly the time-motion structure of judo matches and the athletes’ technical-tactical performance (Gutierrez-Santiago et al, 2011; Gutiérrez-Santiago et al, 2020; Kons et al, 2019; Kons et al, 2021a; Krabben et al, 2018), the athletes’ percentage of victories in competitions over a period of years (Mashkovskiy et al, 2019), the assessment of visual function and its relationship to competitive performance (Krabben et al, 2021a, Krabben et al, 2021b), physical performance (Kons et al, 2021b), world ranking performance (Kons et al, 2021b), and the use of the Delphi analysis approach (Krabben et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies showed, in general, that athletes with higher visual impairment performed more poorly in both competitive skills (e.g., technical variability) and physical performance (e.g., number of throws in a judo specific test) (Gutiérrez-Santiago et al, 2020; Kons et al, 2019; Kons et al, 2021a). Previous evidence-based classifications of judo athletes with visual impairment were based on a relationship between their performance in competition and their performance on visual assessments (Krabben et al, 2020a; Krabben et al, 2020b), with one classification based on expert opinions using a Delphi approach (Krabben et al, 2019).…”
Section: Introductionmentioning
confidence: 99%